SPASMOLYTIC, ANTI-INFLAMMATORY, AND ANTIOXIDANT ACTIVITY OF SALVIA GESNERIFLORA LINDLEY - Gómez-Rivera, Abraham; González-Cortazar, Manasés; Gallegos-García, Ammy Joana; Escobar-Ramos, Armando; Flores-Franco, Gabriel; Lobato-García, Carlos Ernesto (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Salvia gesneriflora Lindley is employed in traditional Mexican medicine for the treatment of several diseases. Materials and Methods: The chromatographic profile of three extracts (SgH, SgD and SgM) of this plant allowed the identification of 11 components in SgH, the presence of rosmarinic (1), chlorogenic (2) and caffeic (3) acids and quercetin glucoside (4) in SgM and of ursolic acid (5) in SgD. The spasmolytic (electrically induced contractions of guinea-pig ileum), anti-inflammatory (edema in mouse ear) and antioxidant potential (DPPH, ABTS and FRAP assays) of the extracts were evaluated. Results: SgM showed the highest percentage of relaxation (80.67 ± 1.633%) with no significant difference (p<0.05) when compared to the reference employed (Papaverine, 76.16 ± 2.44%), the EC50 was 66.89 ± 1.6 μg/mL, respectively for SgH and 26.88 ± 1.9 μg/mL for Papaverine. Anti-inflammatory activity was 71.12 ± 4.9% for SgH, which exerted a similar effect to that of Indomethacin (reference) at the same dose (75.24 ± 2.4%). In the DPPH test, SsM reached the least CI50 (1.16±1.08 μg/mL). For ABTS, SgH reached the least CI50 (1.73 ± 0.5 μg/mL) and for the FRAP assay, SgD showed the highest reductive capacity (1,782.08 ± 2.1 equivalent mM of FeSO4). Conclusion: S. gesneriflora extracts exhibited spasmolytic, anti-inflammatory and antioxidant activities; thus serving as co-adjuvants with regard to knowledge in the traditional medicine of this plant species and its application’s potential in other fields of pharmacy and foods.